Safeguarding Communities: Exploring the Tradition of Tolak Bala in Nagari Bungus - Lisman, Resta; Darmaiza, Darmaiza; Wahyuni, Dwi (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to examine the tradition of tolak bala in Nagari Bungus, including the changes that have occurred, the factors influencing the persistence of the tradition, and the meanings understood by the community regarding the tradition. A qualitative approach was employed, and data were collected through interviews and participatory observation. The findings reveal changes in the tradition of tolak bala in Nagari Bungus, encompassing changes in the surrounding environment and social activities of the community. The tradition of tolak bala has had a positive impact on the community, such as improving their relationship with Allah Swt, enhancing economic conditions, and abandoning negative behaviors. Factors influencing the persistence of the tradition of tolak bala include the community's beliefs and knowledge, religious activities, and the roles of traditional and religious leaders. The community understands the tradition of tolak bala as a means of protection from dangers and as an effort to seek help from Allah Swt to avert calamities. This research provides deeper insights into the tradition of tolak bala in Nagari Bungus and has implications for social and cultural changes in the community. Recommendations are given to the Bungus community and local authorities to preserve and maintain the tradition of tolak bala as a valuable cultural heritage and to conduct further research on this tradition in other regions.